OP132 How A Shared Management Of Home Infusion Can Control Expenditure. (12th January 2018) - Collingnon, Corinne; Fouteau, Emmanuelle; Emery, Gregory; Belghiti, Jacques; Olivier, Cyril
Abstract : INTRODUCTION: In France, medical devices (MDs) for home-based infusion used to be covered by the health insurance system if included on the list of products and services qualifying for reimbursement under a generic description corresponding to a class of products with the same indications. This coverage modality offered no resistance to unnecessary or wasteful spending. Besides, between 2010 and 2015 the expenditure related to these MDs have increased from EUR192million to EUR289million (+50 percent). METHODS: The French National Authority for Health (HAS) has assessed the actual benefit of these MDs which have the same indications as the drugs infused at home. This work led to standardize the infusion types (gravity, elastomeric pump or active system requiring an energy source) and the quantities of MDs needed to carry out the different cares (installation, connection, withdrawal) according to the infusion route. At this step, considering that the priority was to redefine the MDs required at home for each care type, no economical assessment had been conducted. RESULTS: Based on this medical assessment, the Ministry of Health has distinguished three types of infusion and three types of services (home installation, monitoring and consumables) since 2016. In total, twenty-four packages have been set up for reimbursement with non-cumulative rules. Doctors are in charge to prescribe the appropriate packages; providers and nurses determine together the optimal devices needed for each patient according to his environment. CONCLUSIONS: These HAS recommendations on practice standardization have been the keystone for cost negotiations. The new coverage modalities aim to motivate liberal nurses to choose the best fitted products and providers to deliver the right quantities to patients. The expected benefits are an adjusted evaluation of the necessary equipment and a control of health expenditure due to the fixed costs of each infusion package.